Quaternary stratigraphy of southern Vietnam continental margin - Nhu Trung, Nguyen; Viet Dung, Bui; Van Nam, Bui; Nguyen Ha Vu, Pham; Van Kieu, Nguyen (Vietnam Journal of Earth Sciences, 2023)
This study investigates the stratigraphic architectures of the South Vietnam continental margin (SVCM) from the Pliocene to the recent period. We have utilized high-resolution seismic data and sediment core data to achieve this. The study reveals that the Quaternary sequences on the continental margin are bounded by composite erosional surfaces, which were formed due to sub-aerial erosion during periods of sea level fall and subsequent reworking processes during sea level rise. The Quaternary sequence can be divided into two subsequences: the Early Pleistocene and the Middle Pleistocene-Holocene. The Middle Pleistocene-Holocene sequences can be subdivided into six fourth-order sequences, each lasting approximately 100 to 120 thousand years. These sequences are well-preserved on the outer shelf at a modern water depth of around 100 to 120 meters. Seismic stacking patterns indicate that regressive deposits predominantly dominate the Quaternary stratigraphy of the SVCM. This means that sediment deposition during the Quaternary period was more pronounced during periods of sea-level fall. The outer shelf margin of the modern continental margin shows a south-to-southeastward migration of prograding clinoforms, indicating sediment progradation in these directions. The thick Quaternary regressive deposits preserved on the outer shelf are attributed to various factors. These factors include the low shelf gradient, tectonic subsidence, regional hinterland uplift, monsoon strengthening, and high sediment supply from the Palaeo-Mekong Delta during sea-level fall. The interaction of these factors facilitated the accumulation of thick sedimentary deposits during falling sea levels. The mid-late Pleistocene stratigraphy of the SVCM shows similarities to many other continental margins worldwide. These margins are mainly shaped under the influence of asymmetric 4th-order Milankovitch cycles. These cycles are driven by variations in Earth's orbital parameters and are characterized by longer phases of relative sea-level fall followed by shorter periods of stabilization and rise.